Acupuncture for Aromatase Inhibitor–Induced Arthralgia: A Systematic Review. (November 2015) - Bae, Kyeore; Yoo, Hwa-Seung; Lamoury, Gillian; Boyle, Frances; Rosenthal, David S.; Oh, Byeongsang
Background . Aromatase inhibitors (AIs) are commonly used as adjunctive hormone treatment for early breast cancer patients. The major side effect of AIs is arthralgia, which affects adherence. Previous reviews suggested that acupuncture is effective in the management of cancer-related pain. The aim of this review is to evaluate the effects of acupuncture on arthralgia caused by AIs. Methods . This article examined randomized controlled trials (RCTs) measuring the effects of acupuncture on joint symptoms caused by AIs within 8 medical databases till May 2014. The quality of the articles was evaluated according to the Cochrane risk of bias (ROB) tool. Results . Four RCTs were identified in medical journals. Two studies were conducted with manual acupuncture and 2 studies were electroacupuncture. The range of sample size was between 32 and 67. One RCT showed significant improvement in the acupuncture group compared with the sham control group and another RCT showed a statistical difference between the electroacupuncture and waitlist group. The other 2 studies showed no statistical differences between control and acupuncture groups. Two studies conducted blood analysis to elucidate the mechanism of efficacy of acupuncture for arthralgia. The 2 positive studies had a lower ROB and 2 studies had a high ROB. Conclusions . The systematic review suggests that acupuncture has potential benefits to improve arthralgia caused by AIs. However, further trials of adequate sample size, appropriate control group, and longer follow-up are necessary to investigate the efficacy of acupuncture in AI-induced arthralgia.